1976
DOI: 10.1212/wnl.26.6.565
|View full text |Cite
|
Sign up to set email alerts
|

Chronic polyradiculoneuropathy of infancy

Abstract: Two siblings and a third child exhibited a syndrome of progressive muscular weakness and wasting, closely resembling Werdnig-Hoffmann's disease. Autopsy of one of the siblings and the third child showed nearly total absence of myelin sheaths in the cranial and spinal nerve roots, relative preservation of axons, and normal neurons in the motor cranial nerve nuclei and anterior spinal gray matter. The mother of the siblings had bilateral pes cavus, and the father of the third child had a sensory-motor polyneurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, this disorder does not fit into the known classification of hereditary sensorimotor polyneuropathies, though it appears to share some features with Dejerine-Sottas disease (hereditary motor and sensory neuropathy, type I11 [HMSN-111)) and Charcot-Marie-Tooth disease (HMSN-I), but without onion-bulb formation. Neuropathologically, the disorder in our patients most closely resembled the chronic polyradiculoneuropathy of infancy described by Kasman and colleagues [28), and-to a lesser extent-the rapidly progressive congenital hypomyelinating neuropathies described by Karch and Urich 1231…”
Section: Discussionsupporting
confidence: 81%
“…To the best of our knowledge, this disorder does not fit into the known classification of hereditary sensorimotor polyneuropathies, though it appears to share some features with Dejerine-Sottas disease (hereditary motor and sensory neuropathy, type I11 [HMSN-111)) and Charcot-Marie-Tooth disease (HMSN-I), but without onion-bulb formation. Neuropathologically, the disorder in our patients most closely resembled the chronic polyradiculoneuropathy of infancy described by Kasman and colleagues [28), and-to a lesser extent-the rapidly progressive congenital hypomyelinating neuropathies described by Karch and Urich 1231…”
Section: Discussionsupporting
confidence: 81%
“…Less severe cases present in infancy with hypotonia and motor delay ( Phillips et al, 1999 ; McMillan et al, 2010 ) . Complete absence of peripheral nerve myelination does not always predict prenatal or neonatal onset, or early demise, and survival into adulthood is documented ( Kasman et al, 1976 ; Smit et al, 2008 ) . Hence the discrepancy between biopsy findings and clinical features, as well as overlap in genetic causation, makes the distinction between CHN and DSD of limited utility in the diagnosis and management of these patients, particularly in the era of genetic testing in which nerve biopsy may not be required (Fig.…”
Section: Demyelinating Forms Of Cmt With Early Onsetmentioning
confidence: 99%
“…In the first group, the children died in early infancy or early childhood while the second group, although severely handicapped, survived. Lack of evidence for an active myelin breakdown, preservation of axons, and absence of a well formed Schwannian onion bulb and a demyelination-remyelination process, suggested that the cases of congenital hypomyelinating [7][8][9] in/sec of right ulnar nerve neuropathy were different from typical Dejerine-Sottas disease. Based on these observations, it has been hypothesised that in congenital hypomyelinating neuropathy, there is a primary hypomyelination of peripheral nerves secondary to a defect in the Schwann cells.4 This is in contrast to the demyelination which occurs in Dejerine-Sottas disease.…”
Section: Discussionmentioning
confidence: 99%